The effectiveness Assay of Vegetable Pesticides Papaya and Mahogany Leaf Extracts in Pest Control of Spodoptera exigua (Lepidoptera: Noctuidae) on Onion (Allium ascalonicum L) Cultivation - Siregar, Winda Sari; Ginting, Tri Yaninta; Lubis, Najla (Universitas Labuhanbatu, 2024)
Spodoptera exigua is the main pest that attacks the onion crop. S.exigua attack can cause crop failure reaching 57%-100%. The use of natural ingredients from plants for vegetable pesticides such as papaya leaves and mahogany leaves containing secondary metabolite compounds: alkaloids, papain, saponins, tannins, terpenoids, flavonoids and steroids that can damage the feeding activity system and damage the pest growth system which eventually the pest will die. This study uses a non-factorial RAL (Completely Randomized Rack) method with 7 treatments M0= Control, M1= Papaya leaf extract 30%, M2= Papaya leaf extract 60%, M3= Mahogany leaf extract 30%, M4= Mahogany leaf extract 60%, M5 = Papaya leaf extract 15% + mahogany leaf extract 15%, M6= Papaya leaf extract 30% + mahogany leaf extract 30%. The highest mortality result is 72.50% with the treatment of 60% papaya extract vegetable pesticide and the lowest is 27.50% with the treatment of 30% mahogany extract vegetable pesticide. The initial symptoms of death of S. exigua caterpillars are characterized by larvae that are less active in moving, moving to the surface of the container, moving away from the feed, convulsing and finally dying. The mortality of S. exigua larvae at 24 JSA killed a total of 14 larvae and increased with each subsequent treatment. The results of the vegetable pesticide test on natural enemies using extracts that produce the highest percentage of mortality on S. exigua is 100%. This indicates that the extract is safe for the survival of natural enemies. Plant-based pesticides papaya leaf extract, mahogany leaves and a combination of papaya and mahogany leaves have an effect on the mortality of S. exigua caterpillars